Utilizing Visual Media to Improve Conceptual Understanding of Geometry Among Junior High School Students - Supratman; Tundreng, Syarifuddin (EDUPEDIA PUBLISHER, 2025)
Purpose: This classroom action research aimed to improve junior high school students’ conceptual understanding of geometry through the integration of visual media within a cooperative learning framework. Methodology: The study was conducted in two cycles, involving 21 students, and followed the systematic stages of planning, acting, observing, and reflecting. During the pre-cycle, traditional lecture-based instruction led to low engagement and unsatisfactory academic performance, with only 42.86% of students achieving the minimum mastery criterion (KKM). In Cycle I, the implementation of visual media such as diagrams and illustrations combined with cooperative learning activities, led to a modest increase in students’ average scores and engagement levels. However, the mastery rate remained at 52.38%, indicating the need for instructional refinement. In Cycle II, improvements in media quality, structured group facilitation, and enhanced teacher support contributed to significant learning gains. The average class score rose to 80.95, and 90.48% of students met the KKM. Observations also revealed marked improvements in student activeness, collaboration, and confidence in expressing ideas. Findings: The findings confirm that visual media, when effectively integrated into cooperative learning, significantly enhances students' conceptual understanding of geometry-related content. Significance: This research suggests that visual learning strategies should be systematically embedded into science instruction to support deeper comprehension and promote inclusive, student-centered classroom environments.